PHONETICS AS A BRANCH OF LINGUISTICS (American Journal of Interdisciplinary Research and Development, 2022)
This article is mostly focused on the importance of phonetics in Liguistics, how scientists have contributed to the development of this sphere. In addition, it covers some specific aspects of the subject which come in handy for the learners who want to develop their knowledge on it.